2013
DOI: 10.1177/0731684413484817
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on blunt notch behavior of fiber metal laminates containing notch with different shapes

Abstract: In this study, the blunt notch strength of a fiber metal laminate with circular, elliptic and square notch shape has been studied up to failure point. Investigation of the stress concentration does not give a good idea about the strength in anisotropic plates and a failure criterion should be employed to evaluate failure. Therefore, an analytical method has been developed to evaluate stress components and predict the failure around the holes with different shapes. In order to obtain empirical results, specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Epoxy was uniformly spread upon the treated surface of Al‐sheets and woven glass fabrics. The system was maintained at room temperature under pressure for 24 h. As reported by Sadeghpour et al, [ 43 ] no residual stress has been created in the laminate, since the cure cycle was at room temperature. The average thickness of the fabricated GLAREs is 3.9 ±0.15 mm.…”
Section: Experimental Workmentioning
confidence: 99%
“…Epoxy was uniformly spread upon the treated surface of Al‐sheets and woven glass fabrics. The system was maintained at room temperature under pressure for 24 h. As reported by Sadeghpour et al, [ 43 ] no residual stress has been created in the laminate, since the cure cycle was at room temperature. The average thickness of the fabricated GLAREs is 3.9 ±0.15 mm.…”
Section: Experimental Workmentioning
confidence: 99%
“…In prior investigations, the effects of geometric parameters (notch shape and sizes of notch and specimen) [ 9 , 10 , 11 , 12 , 13 , 14 ], types and fractions of constituents [ 15 , 16 , 17 ], and interface adhesion [ 18 ] on mechanical response and damage behavior of FML with blunt notches were experimentally revealed. Moreover, finite element models [ 12 , 13 , 14 , 19 , 20 , 21 , 22 ] and analytical models, e.g., the point and average stress criteria [ 11 , 23 ] and effective crack growth model [ 24 ], were used to predict the notched strength, damage patterns, and damage evolution process.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the initial fiber breakage occurred after the yield of FMLs, followed by the matrix damage. Sadeghpour et al 19 studied the effect of notch shapes on the ultimate notch strength and damage modes of FMLs. Their results exhibited that the circular holes fracture appeared at a point along the longitudinal direction and the square notches fracture occurred at the corner of square along the transverse direction.…”
Section: Introductionmentioning
confidence: 99%